Hypokalemia-Induced Arrhythmias and Heart Failure: New Insights and Implications for Therapy - Skogestad, Jonas; Aronsen, Jan Magnus (Frontiers in Physiology, 2018)
Routine use of diuretics and neurohumoral activation make hypokalemia (serum K+< 3.5 mM) a prevalent electrolyte disorder among heart failure patients, contributing to the increased risk of ventricular arrhythmias and sudden cardiac death in heart failure. Recent experimental studies suggest that hypokalemia-induced arrhythmias are initiated by reduced activity in the Na+/K+-ATPase (NKA), subsequently leading to Ca2+ overload, Ca2+/Calmodulin dependent kinase II (CaMKII) activation and development of afterdepolarizations. In this article, we review the current evidence of mechanisms for hypokalemia-induced triggered arrhythmias, and how molecular changes in heart failure might lower the threshold for these arrhythmias. Finally, we discuss how the recent new insights in hypokalemia-